Sequences, stratigraphy and scenarios: what can we say about the fossil record of the earliest tetrapods? - Friedman, M; Brazeau, MD; Brazeau, MD (2011)
Past research on the emergence of digit-bearing tetrapods has led to the widely accepted premise that this important evolutionary event occurred during the Late Devonian. The discovery of convincing digit-bearing tetrapod trackways of early Middle Devonian age in Poland has upset this orthodoxy, indicating that current scenarios which link the timing of the origin of digited tetrapods to specific events in Earth history are likely to be in error. Inspired by this find, we examine the fossil record of early digit-bearing tetrapods and their closest fish-like relatives from a statistical standpoint. We find that the Polish trackways force a substantial reconsideration of the nature of the early tetrapod record when only body fossils are considered. However, the effect is less drastic (and often not statistically significant) when other reliably dated trackways that were previously considered anachronistic are taken into account. Using two approaches, we find that 95 per cent credible and confidence intervals for the origin of digit-bearing tetrapods extend into the Early Devonian and beyond, spanning late Emsian to mid Ludlow. For biologically realistic diversity models, estimated genus-level preservation rates for Devonian digited tetrapods and their relatives range from 0.025 to 0.073 per lineage-million years, an order of magnitude lower than species-level rates for groups typically considered to have dense records. Available fossils of early digited tetrapods and their immediate relatives are adequate for documenting large-scale patterns of character acquisition associated with the origin of terrestriality, but low preservation rates coupled with clear geographical and stratigraphic sampling biases caution against building scenarios for the origin of digits and terrestrialization tied to the provenance of particular specimens or faunas.